2021
DOI: 10.1186/s13059-021-02344-9
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation microbiology: from comparative genomics to gene function

Abstract: Microbiology is at a turning point in its 120-year history. Widespread next-generation sequencing has revealed genetic complexity among bacteria that could hardly have been imagined by pioneers such as Pasteur, Escherich and Koch. This data cascade brings enormous potential to improve our understanding of individual bacterial cells and the genetic basis of phenotype variation. However, this revolution in data science cannot replace established microbiology practices, presenting the challenge of how to integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 108 publications
0
35
0
Order By: Relevance
“…In this study, we compared a large set of genomes from clinical PA isolates (CF vs. non-CF) and identified mutations that occurred differentially in either CF or non-CF isolates using GWAS based on 31-mer counting ( Fig 8 ). To integrate these findings within a functional genomics context [ 66 ], the impact on bacterial growth- and virulence-associated phenotypes was also assessed. Importantly, PAO1-derived variants, PA5438ΔSLR and YecSΩSLI, exhibited distinct phenotypes in in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared a large set of genomes from clinical PA isolates (CF vs. non-CF) and identified mutations that occurred differentially in either CF or non-CF isolates using GWAS based on 31-mer counting ( Fig 8 ). To integrate these findings within a functional genomics context [ 66 ], the impact on bacterial growth- and virulence-associated phenotypes was also assessed. Importantly, PAO1-derived variants, PA5438ΔSLR and YecSΩSLI, exhibited distinct phenotypes in in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of work has identified many virulence factors, including Microbial Surface Components Recognizing Adhesive Matrix Molecules (MSCRAMMs), the polysaccharide intercellular adhesion (PIA), the Staphylococcal protein A, extracellular proteins such as coagulase, Staphylococcal enterotoxins (SE), exfoliatins (ET), toxic shock syndrome toxin (TSST), staphyloxanthin, hemolysins and Panton Valentine leukocidin (PVL) that have a crucial impact on the pathogenicity of S. aureus infections (35)(36)(37)(38). Genome-wide association studies have been applied to numerous bacterial species (39,40), and identified genes or genetic elements associated with disease that transcend clonal patterns of inheritance (not confined to specific lineages) in Staphylococci. Phenotype filtering techniques have attempted to assess patient risk and predict disease outcome from genetic data based on enrichment for disease-associated traits (12,(41)(42)(43).…”
Section: Despitementioning
confidence: 99%
“…(SE), exfoliatins (ET), toxic shock syndrome toxin (TSST), staphyloxanthin, hemolysins and Panton Valentine leukocidin (PVL) that have a crucial impact on the pathogenicity of S. aureus infections(35)(36)(37)(38). Genome-wide association studies have been applied to numerous bacterial species(39,40), and identified genes or genetic elements associated with disease that transcend clonal patterns of inheritance (not confined to specific lineages) in Staphylococci. Phenotype filtering techniques have attempted to assess patient risk and predict disease outcome from genetic data…”
mentioning
confidence: 99%
“…On the other hand, the known biocatalysts that degrade similar linker bonds in biopolymers such as amidase, hydrolase, and esterase were also found to be effective degraders of C-X group’s plastic types. After the genomic revolution in biological sciences, metagenomic studies have changed the pipeline from microbe discovery to genome mining and further enzyme discovery and engineering (Kobras et al ., 2021). This research work explored the feasibility of a functional bio-based solution for accumulated mixed plastic waste.…”
Section: Introductionmentioning
confidence: 99%